Abdominal drainage versus no drainage after distal pancreatectomy: study protocol for a randomized controlled trial - Kaiser, Jörg; Niesen, Willem; Probst, Pascal; Bruckner, Thomas; Dörr-Harim, Colette; Strobel, Oliver; Knebel, Phillip; Diener, Markus K.; Mihaljevic, André Leopold; Büchler, Markus W.; Hackert, Thilo (Trials, 2019)
The placement of prophylactic intra-abdominal drains has been common practice in abdominal operations including pancreatic surgery. The PANDRA trial showed that the omission of drains following pancreatic head resection was non-inferior to intra-abdominal drainage in terms of postoperative reinterventions and superior in terms of clinically relevant pancreatic fistula rate and fistula-associated complications. The aim of the present PANDRA II trial is to evaluate the clinical outcome with versus without prophylactic drain placement after distal pancreatectomy.
Gesehen am 01.08.2019